Paroxysmal Cranial Dyskinesia and Nail‐Patella Syndrome Caused by a Novel Variant in the LMX1B Gene. Issue 12 (19th September 2020) - Bech, Sara; Løkkegaard, Annemette; Nielsen, Troels T.; Nørremølle, Anne; Grønborg, Sabine; Hasholt, Lis; Steffensen, Gudrun K.; Graehn, Gabor; Olesen, Jess H.; Tommerup, Niels; Mang, Yuan; Bak, Mads; et al.
ABSTRACT: Background: In a Danish family, multiple individuals in five generations present with early‐onset paroxysmal cranial dyskinesia, musculoskeletal abnormalities, and kidney dysfunction. Objective: To demonstrate linkage and to identify the underlying genetic cause of disease. Methods: Genome‐wide single‐nucleotide polymorphisms analysis, Sequence‐Tagged‐Site marker analyses, exome sequencing, and Sanger sequencing were performed. Results: Linkage analyses identified a candidate locus on chromosome 9. Exome sequencing revealed a novel variant in LMX1B present in all affected individuals, logarithm of the odds (LOD) score of z = 6.54, predicted to be damaging. Nail‐patella syndrome (NPS) is caused by pathogenic variants in LMX1B encoding a transcription factor essential to cytoskeletal and kidney growth and dopaminergic and serotonergic network development. NPS is characterized by abnormal musculoskeletal features and kidney dysfunction. Movement disorders have not previously been associated with NPS. Conclusions: Paroxysmal dyskinesia is a heretofore unrecognized feature of the NPS spectrum. The pathogenic mechanism might relate to aberrant dopaminergic circuits. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society. This article has been contributed to by US Government employees and their work is in the public domain in the USA.